2021
DOI: 10.1001/jama.2021.6042
|View full text |Cite
|
Sign up to set email alerts
|

Spike Antibody Levels of Nursing Home Residents With or Without Prior COVID-19 3 Weeks After a Single BNT162b2 Vaccine Dose

Abstract: Recent studies have suggested that, to reach immunity, immunocompetent SARS-CoV-2 seropositive adults may only require 1 dose rather than 2 doses of a messenger RNA vaccine 1,2 ; however, these studies did not include older adults. Older adults living in nursing homes are at higher risk for severe COVID-19, and the immune response to the vaccine may differ from that of younger, healthier adults.We compared IgG antibody levels after a single dose of BNT162b2 (Pfizer-BioNTech) vaccine in nursing home residents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 4 publications
4
39
0
Order By: Relevance
“…Our results demonstrate that a single dose of mRNA vaccine induce high level of S-IgG in the majority of cancer patients with prior SARS-CoV-2 infection. These data are in line with two recent reports among nursing home residents and health care workers previously infected with SARS-CoV-2 [4,5]. However, immunogenicity in cancer patients without previous infection was lower after one dose, but significantly increased within 3 weeks of a BNT162b2 vaccine boost at day 21 after the first dose.…”
Section: Dear Editorsupporting
confidence: 92%
“…Our results demonstrate that a single dose of mRNA vaccine induce high level of S-IgG in the majority of cancer patients with prior SARS-CoV-2 infection. These data are in line with two recent reports among nursing home residents and health care workers previously infected with SARS-CoV-2 [4,5]. However, immunogenicity in cancer patients without previous infection was lower after one dose, but significantly increased within 3 weeks of a BNT162b2 vaccine boost at day 21 after the first dose.…”
Section: Dear Editorsupporting
confidence: 92%
“…13 In a study on 102 residents of a nursing home in France, 36 residents with history of previous Covid infection were found to be positive for S protein IgG while 49.2% showed good immune response after vaccination. 14 In a study by Bradley et al, 15 the level of blocking antibodies were shown to be higher in recently infected group as compared to sero negative individuals. Our study correlates with this study.…”
Section: Discussionmentioning
confidence: 94%
“…Hence the need to conduct special serological surveillance in people aged 65+ or with coexisting chronic diseases, and perhaps to consider the need to take further doses to ensure protective properties. Blain et al [34] focused on a group of nursing home residents and confirmed that one dose of an mRNA vaccine may also be sufficient. At the same time, they pointed out that testing the level of antibodies with neutralizing properties should be carried out for these patients, especially for those with an unknown history of infection.…”
Section: Discussionmentioning
confidence: 96%